Validation study of grace risk score for prognosis in Indian patients with non-STEMI - M., Rangamanikandan; Jelia, Shivcharan; S. R., Meena; Meena, Shyam Bihari; Ajmera, Devendra; Chourasiya, Pramod Kumar; Verma, Ravi; Meena, Manisha (International Journal of Advances in Medicine, 2017)
Background: Cardiovascular disease has emerged as the single most important cause of death worldwide. Every patient of MI has to be stratified according to the risk factors, so that high risk patients can be identified and can be managed effectively GRACE risk score is one of the score used to calculate the risk in MI. Present study was undertaken to correlate GRACE risk score and mortality in non-STEMI. Methods: 200 patients of non-STEMI fulfilling the inclusion criteria admitted in wards of NMCH, Kota were recruited. GRACE risk score was calculated for all patients. Each patient monitored closely throughout their hospitalization. Each component of GRACE risk score was studied for statistical significance. Statistical analysis of correlation was done with chi square test and statistical significance was taken p < 0.05. Results: Mean age is 59.45±8.66 years, with male preponderance, male to female ratio 3:1. Maximum GRACE score is 300 and the minimum score is 86. Patients were categorized into low (74 patients), intermediate (60 patients), high risk (66 patients) according to GRACE score. 14 patients were expired and all of them are in high risk category. GRACE score had sensitivity (100%), specificity (72.04%), positive predictive value (21.2%) and negative predictive value (100%). Serum creatinine (p<0.001), heart rate (p<0.001), blood pressure (p<0.001), Killip class (p<0.001), cardiac biomarkers (p<0.001), ST segment changes (p<0.001) were significantly associated with adverse events. Age>50 (p<0.110) is not significant. Overall grace score demonstrated excellent discrimination (p<0.001), C statistics 0.99, 95% CI 115.742-151.221 for in hospital mortality. Conclusions: This study has shown GRACE risk score is highly accurate in predicting in hospital mortality in patients of non-STEMI. We should routinely use GRACE risk score in our hospital settings to identify the high-risk patients to decrease mortality.